Latitudinal, Diurnal, and Seasonal Variations in the Accuracy of an RTK Positioning System and Its Relationship With Ionospheric Irregularities - A. F. Follestad; L. B. N. Clausen; J. I. Moen; K. S. Jacobsen (Space Weather)
Abstract The Norwegian Mapping Authority operates a network real time kinematic (RTK) system called CPOS, a positioning service providing centimeter level accuracy aimed at commercial users, for example, in civil engineering, excavation, and surveying. CPOS is based on multiple Global Navigation Satellite Systems (multi‐GNSS) in addition to base stations to provide correction data. CPOS position accuracy is subject to disturbances arising from space weather phenomena, which can disturb and disrupt GNSS signals. Studies have shown that CPOS performance is sensitive to the presence of plasma irregularities, usually quantified by the rate of change of total electron content index (ROTI). This study investigates the performance of CPOS over a 3‐year period, and its relationship with ionospheric irregularities. In a statistical analysis, we observe that CPOS position errors have seasonal, diurnal, and latitudinal variations. The most frequent position errors occur around magnetic noon and are of moderate severity, while the largest position errors occur around night‐time, agreeing well with climatology studies on GNSS scintillations. Additionally, we investigate ionospheric irregularities as characterized by the rate of TEC index (ROTI). We find that there is a significant correlation between CPOS accuracy and ROTI, but that there are also other contributing factors.